Development of a TPACK-Based E-Module to Support Students' Mathematical Literacy Skills - Ulum, Achmad Miftachul; Az-Zahrawani, Muhammad Sulthon Kurnia; Rifqy, Muhammad Iqbal (AS-SABIQUN, 2025)
Mathematical literacy is very important in the industrial era 4.0, but international surveys such as PISA show that Indonesian students have poor mathematical abilities. Therefore, new teaching materials are needed. Developing a TPACK-based e-module to promote mathematical literacy is the goal of this study. A 4D development model—define, design, develop, and disseminate—is used in the study. Analyzing learning demands is part of stage define, and designing technology-based e-modules is part of stage design. Following validation by specialists in language, media, and materials, the develop stage produces an e-module that is prepared for testing through adjustments based on validator suggestions. The disseminate stage involves limited testing and distribution to students. Researchers used descriptive analysis techniques in processing the data obtained. The validation results show that the e-module is very valid with a score of 95% for language, 92% for media, and 100% for material. Teacher responses were in the " Highly good" category (95%), while student responses were in the "good" category (73%). This research proves that TPACK-based e-modules are effective in supporting learning, providing solutions to improve students' mathematical literacy, and are relevant for application in technology-based learning.